Who was nelson mandela? - Pollack Pam; Pollack Pam (UK Penguin Workshop, 2014)
As a child he dreamt of changing South Africa; as a man he changed the world. Nelson Mandela spent his life battling apartheid and championing a peaceful revolution. He spent twenty-seven years in prison and emerged as the inspiring leader of the new South Africa. He became the country$1 (Bs first black president and went on to live his dream of change. This is an important and exciting addition to the Who Was...? series.s